Reduction in disparity for pneumonia hospitalisations between Australian indigenous and non-Indigenous children. Issue 6 (22nd January 2011) - Moore, Hannah C; Lehmann, Deborah; de Klerk, Nicholas; Jacoby, Peter; Richmond, Peter C
Abstract : Background: In the 1990s pneumonia hospitalisation rates in Western Australia (WA) were 13 times higher in Indigenous children than in non-Indigenous children. Rates of invasive pneumococcal disease in Indigenous children declined following the introduction in 2001 of 7-valent pneumococcal conjugate vaccine (7vPCV) in a 2–4–6 month schedule with an 18-month pneumococcal polysaccharide booster (PPV). We investigated population trends for pneumonia hospitalisations between 1996 and 2005. Methods: Population-based retrospective data linkage cohort study of singleton live births from 1996–2005. Hospitalisations for acute lower respiratory infections in Indigenous and non-Indigenous children less than 5 years of age were extracted and trends in age-specific incidence rates were examined using log-linear modelling. Results: From 245 249 births (7.1% Indigenous), there were 7727 pneumonia episodes. Between 1996 and 2000 and 2001 and 2005 all-cause pneumonia hospitalisations fell by 28–44% in Indigenous children aged 6–35 months with no equivalent decline in non-Indigenous children or for other acute lower respiratory infections. Incidence rate ratios for pneumonia comparing Indigenous with non-Indigenous children aged 6–11 months fell from 14.6 (95% CI 12.3 to 17.2) in 1996–2000 to 9.9 (8.4 to 11.6) in 2001–2005. Log-linear modelling showed a steady decline in Indigenous children of 9%/annum (5–12%) at age 12–23 months for all-cause pneumonia and 37%/annum (20–50%) at age 6–11 months for pneumococcal pneumonia from 1996 to 2005, including the years prior to introduction of pneumococcal vaccines. Conclusions: Pneumonia hospitalisations and the disparity between Indigenous and non-Indigenous children has declined by a third. The unique Australian pneumococcal vaccine programme is likely to have had a significant effect but changes in socioeconomic factors have also contributed to the declines.